Compassion fatigue and compassion satisfaction among nurses/midwives caring parents with pregnancy loss or infertility: a cross-sectional study - Liu, Siyu; Han, Hongmei; Athurupana, Rukmali; Yang, Titi; Nakatsuka, Mikiya (Frontiers in Public Health, 2025)
ObjectivesThe study aimed to assess the prevalence and potential factors associated with compassion fatigue and compassion satisfaction among nurses/midwives who support parents with pregnancy loss or infertility.MethodsA total of 370 nurses and midwives were recruited from 43 hospitals and clinics in the Chugoku-Shikoku region of Japan. We collected data using a demographic survey, the Professional Quality of Life Scale, and the Adolescent Resilience Scale. Descriptive statistics, t-tests, one-way ANOVA, Pearson correlation analyses, and multiple linear regression were conducted for data analysis.ResultsThe participants reported moderate level for compassion satisfaction (83.8%) and burnout (77.3%), and a low level for secondary traumatic stress (51.4%). The predictors explained 42.9% predicted 42.9, 49.1, and 16.9% of the variance in the model of compassion satisfaction, burnout, and secondary traumatic stress, respectively.ConclusionNurses/midwives demonstrated moderate levels of burnout and low levels of secondary traumatic stress. Resilience, marital status, education background, working characteristics, organizational support, knowledge sufficiency, and the practice of grief care were identified as factors associated with compassion fatigue and compassion satisfaction among nurses/midwives.